Data integration and conceptual modelling of the Larderello geothermal area, Italy. (September 2017) - Gola, Gianluca; Bertini, Giovanni; Bonini, Marco; Botteghi, Serena; Brogi, Andrea; De Franco, Roberto; Dini, Andrea; Donato, Assunta; Gianelli, Giovanni; Liotta, Domenico; Manzella, Adele; Montanari, Domenico; et al.
Abstract: In the frame of the Integrated Method for Advanced Geothermal Exploration (IMAGE) Project, a reliable exploration and resource assessment workflow was implemented on the basis of an integrated and multidisciplinary approach. Our study addressed to a better understanding of the thermal structure of the deepest part of the Larderello geothermal field (Southern Tuscany, Italy) by integrating structural, geological, geochemical, geochronological, petrological and geophysical data. With the aim to characterize the reservoir located nearby an important seismic reflector (the K-horizon), we systematized the available data and, successively, we applied a numerical thermal modelling approach to test our hypotheses and concepts.